Pengaruh Penagihan Pajak Dengan Surat Teguran dan Surat Paksa Terhadap Kepatuhan Wajib Pajak di Kantor Pelayanan Pajak Pratama Padang Satu - Nila Sari; Dewi Zulvia; Ratna Widayati; Renil Septiano (JURNAL PUNDI, 2018)
The purpose of this study is to examine the effect of tax collection by the forced letter and letter of reprimand against taxpayer compliance at the Tax Office Pratama padang. This research uses multiple linear regression analysis. The result of simple regression analysis shows that the coefficient value of letter warning variable is 0,449. The strike variable has a t test value (titung) of 6.863 with a significance level of 0.000 <0.05. This shows that there is a positive and significant effect of tax collection with letters of reprimand against taxpayer compliance in KPP Pratama Padang. The result of simple regression analysis shows that the coefficient value of the forced letter variable is 0.226. The variable of forced letter has a value of t test (titung) of 2.155 with a significance level of 0.035> 0.05. This shows that there is a positive and significant effect of tax collection with letters of reprimand against taxpayer compliance in KPP Pratama Padang. The results of this research also show that the significance value of the F test is 0.000 which has a value less than 0.05. This means that the collection of taxes with letters of reprimand and forced mail together have a significant effect on taxpayer compliance in KPP Pratama Padang. From result of determination test show that coefficient value of Adjusted R Square is equal to 0,442, it means 44,2% taxpayer compliance variable can be explained by tax collection variable with letter of warning and forced letter. While the rest (100% - 44.2% = 55.8%), influenced by other variables associated with taxpayer compliance Keywords: tax collection, letter of reprimand, forced letter, taxpayer compliance